2021
DOI: 10.1007/s12274-021-3823-z
|View full text |Cite
|
Sign up to set email alerts
|

Structural revolution of atomically dispersed Mn sites dictates oxygen reduction performance

Abstract: An efficient preparation and local coordination environment regulation of isolated single-atom sites catalysts (ISASC) for improved activity is still challenging. Herein, we develop a solid phase thermal diffusion strategy to synthesize Mn ISASC on highly uniform nitrogen-doped carbon nanotubes by employing MnO 2 nanowires@ZIF-8 core-shell structure. Under hightemperature, the Mn species break free from core-MnO 2 lattice, which will be trapped by carbon defects derived from shell-ZIF-8 carbonization, and immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…MnOOH rods exhibited the characteristic peaks of pure MnOOH (PDF #41-1379) with good crystallinity (Figure S4a). Moreover, the diffraction peaks at 34.9, 40.5, and 58.7° of MnO-NC and MnO were consistent with (111), (200), and (220) planes of pure MnO (PDF #07-0230), respectively (Figure a) . NCs only exhibited two broad peaks at around 25 and 41°, indicating the amorphous form of carbon.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…MnOOH rods exhibited the characteristic peaks of pure MnOOH (PDF #41-1379) with good crystallinity (Figure S4a). Moreover, the diffraction peaks at 34.9, 40.5, and 58.7° of MnO-NC and MnO were consistent with (111), (200), and (220) planes of pure MnO (PDF #07-0230), respectively (Figure a) . NCs only exhibited two broad peaks at around 25 and 41°, indicating the amorphous form of carbon.…”
Section: Resultssupporting
confidence: 53%
“…Similarly, Wu et al. reported the synthesis of isolated single atomic Mn sites on N-doped nanotubes via a solid thermal diffusion strategy . Nonetheless, a facile thermal migration method is still lacking to construct efficient ORR catalysts for their widespread application.…”
Section: Introductionmentioning
confidence: 99%
“… 19 21 Among them, the most reported SACs are limited to transition-metal atoms (Fe, Co, Ni, Cu, etc.) supported by heteroatom N-doped carbonaceous materials, which can be applied to the catalysis of a wide range of electrochemical reactions of ORR, 22 28 nitrogen reduction reaction (NRR), 29 34 carbon dioxide reduction reaction (CO 2 RR), 35 41 hydrogen reduction reaction (HER), 42 44 OER, 8 , 45 , 46 etc. The single metal atom and its coordination environment are usually modeled by a MN 4 moiety having a metal center coordinated with four N atoms.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the designed hollow structure plays an important role in accelerating the kinetics and improving performance. He et al [102] synthesized a series of noble-metal (Ir, Pt, Ru, Au and Pd) single atoms immobilized on hollow nanotubes derived from a zirconiumporphyrinic MOF, which are equipped with square-planar four coordinate porphyrin units to anchor a single atom. This unique single-shell hollow structure was beneficial for fast mass diffusion.…”
Section: Sacs Supported On Single-shell Hollow Materialsmentioning
confidence: 99%